2014
DOI: 10.1175/jpo-d-13-0191.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Eddy-Induced Modification of Subtropical Mode Water during the Kuroshio Extension System Study

Abstract: From 2004From to 2006 an observational array of current-and pressure-recording inverted echo sounders (CPIES) were deployed as part of the Kuroshio Extension (KEx) System Study (KESS). KESS observed a transition from a weakly meandering (''stable'') to strongly meandering (''unstable'') state (Qiu and Chen). As the KEx made this transition, potential vorticity (PV) observed within the southern recirculation gyre (SRG) rapidly increased from January to July 2005. In this study, the authors diagnose eddy PV fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The diffusion coefficient κ l is assumed to be vertically constant in the ML. Recent observational studies have provided different results concerning the magnitude of the lateral eddy diffusion coefficient κ l in the Northwestern Pacific Ocean (e.g., Abernathey & Marshall, 2013; Bishop & Watts, 2014; Forget et al., 2015; Groeskamp et al., 2020; Liu et al., 2012). The different coefficients indicate that the magnitude of lateral eddy diffusivity varies with the canonical value on the order of 10 3 m 2 s −1 in the Northwestern Pacific Ocean (125°E−180°, 20°N–40°N).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion coefficient κ l is assumed to be vertically constant in the ML. Recent observational studies have provided different results concerning the magnitude of the lateral eddy diffusion coefficient κ l in the Northwestern Pacific Ocean (e.g., Abernathey & Marshall, 2013; Bishop & Watts, 2014; Forget et al., 2015; Groeskamp et al., 2020; Liu et al., 2012). The different coefficients indicate that the magnitude of lateral eddy diffusivity varies with the canonical value on the order of 10 3 m 2 s −1 in the Northwestern Pacific Ocean (125°E−180°, 20°N–40°N).…”
Section: Methodsmentioning
confidence: 99%
“…The sensitivity of eddy-induced subduction to an uncertain parameter, the lateral eddy diffusion coefficient κ l , is quantified in the impact of choice of finite magnitude on the subduction picture according to Equation 11. Here, we restricted the constant diffusion coefficient κ l to the lower (κ l = 1,000 m 2 s −1 ) and upper (κ l = 3,000 m 2 s −1 ) limits as found in previous studies (e.g., Abernathey & Marshall, 2013;Bishop & Watts, 2014;Forget et al, 2015;. In addition, the spatially varying eddy diffusion coefficient κ l at the surface ML, estimated from Groeskamp et al (2020), is also used to calculate the eddy-induced subduction in the Northwestern Pacific Ocean (125°E−180°, 20°N-40°N).…”
Section: 1029/2022jc018945mentioning
confidence: 99%
“…They found that the enhanced eddies affect STMW by altering the stratification in the upper ocean, which impedes the formation of a deep winter mixed layer (hence, the source for STMW), and by providing a high-potential vorticity source that mixes with the surrounding low-potential vorticity STMW. Bishop and Watts (2014) pointed out that cold-core ring formation was the mechanism driving the cross-frontal exchange of high-potential vorticity water from the northern side of the Kuroshio to the south. Xu et al (2016) deployed 17 daily sampled Argo floats to study the effect of anticyclonic eddies on STMW south of the KE.…”
Section: Introductionmentioning
confidence: 99%
“…Transport variability of the Antarctic Circumpolar Current (ACC)—the largest ocean current system on the globe—has been monitored in Drake Passage already 40 years ago (Nowlin et al, ) and continues until present days also with the help of in situ OBP recorders (Meredith et al, ). The dynamics of the Kuroshio extension off the Japanese coast—a region characterized by high eddy kinetic energy due to the confluence of warm, salty subtropical and cold, fresh subpolar waters—were recently studied in detail with an array of current meters and pressure recording inverted echo sounders (Bishop & Watts, ). And finally, the Atlantic Meridional Overturning Circulation—responsible for poleward heat transport and the associated rather mild climate in western Europe—is monitored routinely by the RAPID array at 26°N with a series of in situ OBP sensors aligned along the gradient of the continental shelf (McCarthy et al, ).…”
Section: Introductionmentioning
confidence: 99%